Digital Work Culture Transformation and Its Effect on Management Control Effectiveness in Medium Sized Enterprises in Indonesia - Budwi Brontosantoso; Wahyudi; Murti Wisnu Ragil (Jurnal Ragam Pengabdian, 2026)
Medium-sized companies in Jakarta's buffer area face the complexity of organizational control along with the adoption of a work system based on digital technology. Although various companies have adopted ERP, HRIS, digital accounting systems, and online collaboration applications, management control practices are still in many cases still dominated by traditional SOPs and hierarchical oversight. This study aims to analyze the influence of digital work culture transformation on the effectiveness of management control in medium- sized companies in the manufacturing and service sectors in the Bekasi, Tangerang, and Depok regions. The research uses a mixed methods approach with a sequential explanatory design. The quantitative stage was carried out through a survey of 100 respondents consisting of middle managers, supervisors, and unit heads, with multiple linear regression analysis. The qualitative stage was carried out through semi-structured interviews with 6 key informants, namely operational managers, human resource managers, and digital transformation leaders. The results show that the transformation of digital work culture has a significant effect on the effectiveness of management control, especially through increasing system-based work transparency, real- time performance monitoring, and data-based compliance. Qualitative findings reveal that digital work culture serves as an informal control mechanism that reinforces formal control without relying on direct supervision. This research contributes to the development of the management control literature by affirming the role of digital work culture as a key element in the design of the management control system of mid-sized companies in the digital era.